Electrophysiological activity pattern of mouse hippocampal CA1 and dentate gyrus under isoflurane anesthesia - Wang, Rui; Zhang, Linzhong; Wang, Xia; Li, Wen; Jian, Tingliang; Yin, Pengcheng; Wang, Xinzhi; Chen, Qianwei; Chen, Xiaowei; Qin, Han (Frontiers in Cellular Neuroscience, 2024)
General anesthesia can impact a patient's memory and cognition by influencing hippocampal function. The CA1 and dentate gyrus (DG), serving as the primary efferent and gateway of the hippocampal trisynaptic circuit facilitating cognitive learning and memory functions, exhibit significant differences in cellular composition, molecular makeup, and responses to various stimuli. However, the effects of isoflurane-induced general anesthesia on CA1 and DG neuronal activity in mice are not well understood.In this study, utilizing electrophysiological recordings, we examined neuronal population dynamics and single-unit activity (SUA) of CA1 and DG in freely behaving mice during natural sleep and general anesthesia. Our findings reveal that isoflurane anesthesia shifts local field potential (LFP) to delta frequency and reduces the firing rate of SUA in both CA1 and DG, compared to wakefulness. Additionally, the firing rates of DG neurons are significantly lower than CA1 neurons during isoflurane anesthesia, and the recovery of theta power is slower in DG than in CA1 during the